A Revision of Parasecia (Trombidiformes: Trombiculidae) With a Description of a New Species, a New Genus and a Key to Species. Issue 1 (26th August 2020) - Bassini-Silva, Ricardo; Jacinavicius, Fernando de Castro; Oliveira, Mariana; Peinado, Laura Contreras; Faxina, Claudenice; Moreira-Lima, Luciano; Welbourn, Cal; Ochoa, Ronald; Fischer, Erich; Hingst-Zaher, Erika; Famadas, Kátia M; Faccini, João Luiz Horacio; et al.
Abstract: Chiggers of the genus Parasecia Loomis parasitize birds, mammals, and reptiles in the Nearctic and Neotropical regions. In the present review, we examined 18 species previously included in the genus, 15 of them being retained in the genus Parasecia, one genus is created, Nahuacarus bulbocalcar n. gen. (Trombidiformes: Trombiculidae), and new combinations are proposed for two species: Lorillatum lasiurus n. comb. and Lorillatum orphana n. comb. (Trombidiformes: Trombiculidae). In addition, Parasecia kansasensis (Loomis) (Trombidiformes: Trombiculidae) is synonymized with Parasecia gurneyi (Ewing) (Trombidiformes: Trombiculidae), Parasecia gilbetoi n. sp. (Trombidiformes: Trombiculidae) is described and new locality and host records are added for Parasecia chara (Wharton), Parasecia longicalcar (Brennan and Jones), Parasecia manueli (Brennan and Jones), and Parasecia thalurania (Brennan) (Trombidiformes: Trombiculidae).